The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1590/s0100-41582003000600007
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização enzimática e patogenicidade cruzada de Colletotrichum spp. associados a doenças de pós-colheita

Abstract: A antracnose, causada por Colletotrichum spp., pode ocasionar grandes perdas a nível de campo e em pós-colheita sobre diversas culturas e seus produtos. O presente trabalho teve por objetivos testar a patogenicidade cruzada de isolados de C. gloeosporioides do caju (Anacardium occidentale) (CAJ), manga (Mangifera indica) (MG), mamão (Carica papaya) (MM), maracujá (Passiflora edulis) (MR) e C. musae da banana (Musa spp.) (BAJ); avaliar a produção de enzimas extracelulares (amilolítica, celulolítica, lipolítica … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 13 publications
0
2
0
7
Order By: Relevance
“…Isoenzyme profile analysis has been useful to investigate genetic diversity within Colletotrichum. Lima Filho et al (2003), using EST and ACP enzyme patterns obtained by PAGE, reported intraspecific variability among C. gloeosporioides isolates from several tropical fruits. Additionally, Rios et al (2004) successfully used the EST, ACP, ALP and MDH isoenzymes, to confirm the existence of genetic variability in C. lagenarium.…”
Section: A B Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Isoenzyme profile analysis has been useful to investigate genetic diversity within Colletotrichum. Lima Filho et al (2003), using EST and ACP enzyme patterns obtained by PAGE, reported intraspecific variability among C. gloeosporioides isolates from several tropical fruits. Additionally, Rios et al (2004) successfully used the EST, ACP, ALP and MDH isoenzymes, to confirm the existence of genetic variability in C. lagenarium.…”
Section: A B Cmentioning
confidence: 99%
“…Isoenzymatic analyses were successfully used to study intraspecific variations and also to establish interspecific differences among Colletotrichum species (Bonde et al, 1991, Rego et al, 1994Lima & Menezes, 2002;Lima Filho et al, 2003;Horvath & Vargas, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Esses fatores podem contribuir também para aumentar a suscetibilidade das plantas a certos patógenos e afetando a incidência e a severidade das doenças (2, 18). Em contrapartida, altos teores de umidade são benéficos ao fruto na cultura do mamão, pois influenciam na manutenção da turgidez e na redução da perda de água (1, 14,19,30).…”
Section: Introductionunclassified
“…Outras enzimas extracelulares secretadas por espécies fitopatogênicas, e que também podem ser importantes na patogênese, incluem: cutinases, celulases, hemicelulases, proteases, lipases, xilanases, glucanases, manases, xilosidases e arabinosidases (5, 7, 17,26,27,29,33,37).…”
Section: Introductionunclassified
“…A atividade patogênica de alguns fungos, conforme Hancock & Millar (12), está diretamente relacionada com a sua capacidade enzimática. Em certos casos, correlações entre a presença de certas atividades enzimáticas e o desenvolvimento de sintomas de doenças têm sido encontradas (5, 7, 16,17,22). Estudos dessa natureza são importantes porque podem estimular a obtenção de mutantes tipo perda-de-função, gerando assim informações consistentes acerca do papel das exoenzimas.…”
Section: Introductionunclassified